Communication about sex-reproductive health issues with adolescents: a taboo among Malaysian parents? - Ismail, Khamsiah; Abd Hamid, Siti Rafiah (European Center for Science Education and Research, 2016)
Young people need to establish their identity and develop the ability to make their own decisions and plan for their future life. This establishment is an important process which is facilitated by good communication with parents and family, especially regarding problem-solving skills. Through open communication they can express their ideas freely, which then leads to family satisfaction and lessen conflict. Parent-child communication would heighten family cohesion, contentment, psychological wellbeing and at the same time thwart detrimental life consequences for adolescents. Research has also revealed that family environment and communication is in fact a predictive factor for risky behaviour in young people around the world. Thus, effective communication is imperative in promoting good family functioning. Many parents are still reluctant to discuss sexrelated issues with their children openly. Parents found that such talks are hard to initiate. This study has two-pronged objectives, first, to examine sexuality and reproductive health that adolescents communicate to their parents and second, is to explore adolescents’ views on communication with parents on matters related to the topics.The population of this study was lower secondary school students who came from four different zones in Peninsular Malaysia and East Malaysia. Quantitative data was collected from 504 respondents from urban, semi urban and rural geographical school locations for study via multistage stratified sampling procedure. This survey employed two sets of constructs from the Highly At-Risk Behaviours Questionnaire (a questionnaire to gauge adolescents highly at-risk behaviours) - HARBQ. Descriptive (means, standard deviation and percentages) and inferential statistical analyses in this study revealed several interesting findings. Interestingly Malaysian teens were found rarely discussed issue related to sex and reproductive health with their parents. Ironically, they were open for discussion about these matters with their parents as long as would not turn them down. The respondents were also found positive in that they could communicate with their parents on matters related sexual and reproductive health issues. Findings from this study provide crucial information which may help improvise existing interventions and communication of knowledge and skills on reproductive health to adolescents especially by parents. Counsellors could use the information to provide effective treatment; intervention and preventive plan for teenagers to enable them to cope with the issues and in reducing unwanted consequences that may arise in the future.